1957
DOI: 10.1021/ac60125a004
|View full text |Cite
|
Sign up to set email alerts
|

Spectrophotometric Determination of Iron with 2-Fluorobenzoic Acid

Abstract: The color of the water-soluble amethyst complex formed by the reaction of ferric ions with 2-fluorobenzoic acid can be used as the basis of a spectrophotometric method for the determination of iron. The effect of pH, concentration of reagents, and the presence of diverse ions are discussed. Results similar to those obtained by the salicylic acid method for the determination of iron can be expected, with the advantage that only the ferric ion reacts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1958
1958
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…"Metallurgical Analysis" (208), "Kolorimetrlsche Analyse" (288), "Analisi Fotometría" (75), and "Kolorimetrie" (325) are foreign publications. Interscience has announced "Colorimetric Determination of Nonmetals" (69). An "Ultraviolet and Visible Absorption Spectra Index for 1930-54" has been published (208).…”
Section: Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…"Metallurgical Analysis" (208), "Kolorimetrlsche Analyse" (288), "Analisi Fotometría" (75), and "Kolorimetrie" (325) are foreign publications. Interscience has announced "Colorimetric Determination of Nonmetals" (69). An "Ultraviolet and Visible Absorption Spectra Index for 1930-54" has been published (208).…”
Section: Applicationsmentioning
confidence: 99%
“…Numerous new reagents continue to be proposed for the determination of iron, the following being selected as most worthy of mention. Iron(III) gives a red color with 5-sulfoanthranilic acid (598), a purple color with 2-fluorobenzolc acid (69), an orange-red color with /S-resorcylic acid (564), a red-violet color with ethylenediamine-bis (sulfosalicylaldehyde) (373), an orange color with paminosalicylic acid (374), a blue color with 4-amino-4-methoxydiphenylamine (127), and a red color with thenoyltrifluoroacetone (264). Iron(II) gives a green color with o-nitrosoresorcinol monomethyl ether (412, 543), and a purple color with 2,6-bis(4-phenyl-2pyridyl)-4-phenylpyridine (477).…”
mentioning
confidence: 99%
“…It was also shown that some bacterial strains use fluorobenzoates as the sole source of carbon and energy [ 6 , 7 ], and the metabolic and catabolic processes involving these compounds have been extensively studied [ 7 , 8 , 9 , 10 , 11 , 12 ]. Due to its complexing ability, the ortho -substituted fluorobenzoic acid (2-fluorobenzoic acid) has been for long used in the quantitative determination of iron in aqueous solution [ 13 ]. In its turn, the chloro-substituted benzoic acids are amongst the more versatile precursors or intermediates in the synthesis of pesticides [ 14 ].…”
Section: Introductionmentioning
confidence: 99%